Jornalistas da resistência: histórias de vida de jornalistas negras do Rio Grande do Norte - Souza, Allyne Camylla Paz de (2022)
Throughout history, women have struggled to gain space and recognition for their work. In this race of society's privileges, black women, especially those from the periphery, are the ones who suffer the most from this erasure and invisibility. It is necessary to reflect on these privileges and question what are the places that the black population occupies around us and also outside of it. In this context, the proposal of the documentary “Aqui tem jornalista negra”, final product of the research for the Professional Master in Journalism, was to understand how the social markers of race and gender directly influence the lives of black journalists from the perspective of the life history of four black journalists residing in Natal, capital of the state of Rio Grande do Norte, located in the Northeast region of Brazil. The work was based on key concepts for understanding the aspects studied such as intersectionality (AKOTIRENE, 2019), (COLLINS, 2017) and structural racism (ALMEIDA, 2019). The ideas related to black feminism were based on the thinking of (GONZALEZ, 2020) and (CARNEIRO, 2003). To carry out the work, life history was used as a methodology (MARTINEZ, 2008) and four women with professional experience in Rio Grande do Norte journalism reported their trajectories, challenges and difficulties until they conquered a space of recognition in the profession. The choice to disseminate the results through the documentary format was due to the fact that this platform facilitates the access to this work for a greater number of people. The reports of the professionals interviewed show how structural racism has hindered the access and rise of black women in professions with greater prestige and visibility, such as journalism.